Investigations of mechanical properties and chemical changes occurring during welding of thermally modified ash wood. Issue 1 (2nd January 2020) - Amirou, Siham; Pizzi, Antonio; Delmotte, Luc
Abstract: Heat treatment of wood appears as an ecological and environmentally friendly alternative in the field of wood treatment. Generally, thermal modification increase dimensional stability by reduces of hygroscopicity and water absorption but it makes it difficult to bonding in some application. During welding, changes in the morphological, chemical, and physical properties of the wood cell wall are observed due to the compression and high temperatures produced by welding. Also, the degradation of cell wall in the wood causes some mechanical properties are reduced. This modification appears without any effect on the linear welding of thermal-ash wood. Scanning electron microscopy (SEM) and nuclear magnetic resonance (NMR) were used for evaluation of properties of wood–welding systems and their interactions. The mass spectrometry (MS) analysis was used to identifying the organic degradation products emitted during welding of thermo-ash. The results of experiments show that the use of friction welding for the bonding of thermal ash wood in dry conditions was possible, and we had good results. The best combination was with a welding time of 3.5 s devised to 0.5 s and 3 s and welding pressure 2.5 and 4 MPa, respectively. The result obtained is comparable to the result obtained with EPI adhesives. Welding time greater than 3.5 MPa negatively affects the welding quality and gives low the mechanical strength.